2011
DOI: 10.1111/j.1574-6968.2011.02371.x
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution melting for analysis of short sequence repeats in Mycobacterium avium subsp. paratuberculosis

Abstract: Analysis of micro- and minisatellite loci is widely used in sub-typing of Mycobacterium avium subsp. paratuberculosis. Microsatellite (short sequence repeat, SSR) loci have shown highest discriminatory power, but direct sequencing of amplicons is required for correct assignment of the repeat number. We developed an alternative method to sequencing, focusing on the SSR8 locus (constituted by GGT triplets from three to six repeats). The approach is based on asymmetric quantitative PCR, followed by high-resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…Only three distinct MV types were observed for all strains among which the MV 2 type was found to be specific to the bisontype group. Among these 5 loci, only MIRU-VNTR 1067 was found to be polymorphic, in agreement with other studies (30,48). Considering the results of the present and previous studies, MIRU 1 and MIRU 4 may be excluded from future studies since these loci appear monomorphic for cattle strains from different areas of the world (24,31).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Only three distinct MV types were observed for all strains among which the MV 2 type was found to be specific to the bisontype group. Among these 5 loci, only MIRU-VNTR 1067 was found to be polymorphic, in agreement with other studies (30,48). Considering the results of the present and previous studies, MIRU 1 and MIRU 4 may be excluded from future studies since these loci appear monomorphic for cattle strains from different areas of the world (24,31).…”
Section: Discussionsupporting
confidence: 78%
“…In agreement with other studies, MLSSR typing was found to be the most discriminatory typing method (17,44,48). However, different groups have used distinct sets of SSR loci.…”
Section: Discussionsupporting
confidence: 75%
“…To the best of the authors' knowledge, this is the first article describing the application of HRM analysis for SSR genotyping in fungal pathogens. Genotyping with HRM analysis is a robust and reproducible method, and may be an appropriate alternative to using a capillary sequencer when loci show a reduced number of alleles (Ricchi et al ., ). In the current work, HRM analysis was able to detect both SSR length and SNP‐based polymorphisms in SSR, SSR flanking regions and homopolymeric traits, overcoming the issue related to allelic size homoplasy.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have combined HRMA with real-time PCR assays for rapid detection and identification of clinically important bacteria (Ajitkumar et al, 2012;Chen et al, 2011;Cheng et al, 2006, Ricchi et al, 2011Choi et al, 2010;Douarre et al, 2012;Pang et al, 2011;Pietzka et al, 2009;Tortoli, 2009;Won et al, 2010;Yang et al, 2009). The literature suggests that a combined real-time PCR-HRMA assay is a novel and rapid technique suitable for the genotyping of drug-resistant isolates of M. tuberculosis (Chen et al, 2011;Pietzka et al, 2009;Ramirez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%